ETIKA PROFESI DAN PERLINDUNGAN HUKUM: STUDI PADA PRAKTIK MEDIS DI INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
Professional ethics and legal protection are two important aspects of medical practice in Indonesia. Professional ethics serve as moral guidelines for medical personnel in carrying out their duties, particularly in maintaining integrity, patient confidentiality, and health service standards. Meanwhile, legal protection helps ensure that medical personnel have legal certainty in their work, especially when facing potential conflicts or claims from patients. This study highlights the importance of synergy between professional ethics and legal protection in creating a fair, professional, and high-quality healthcare ecosystem. By combining ethical and legal approaches, medical practice in Indonesia can provide optimal benefits for patients while protecting the rights of medical personnel. Emphasis on education and socialisation regarding the roles, rights, and obligations of each party is also a solution to reduce tension between patients and medical personnel.